The Effects of Policy Implementation Uncertainty on Groundwater Extraction. (August 2016) - Bian, Dacheng; Williams, Ryan B.; Benson, Aaron; Segarra, Eduardo
Abstract: Concerns about the high rate of depletion of the Ogallala Aquifer in the Southern High Plains of Texas (Texas High Plains) in recent years have led to the enactment of policies designed to slow down water extraction and increase the usable life of the aquifer. However, policy implementation has not been uniform across the aquifer, leaving some farmers in portions of the aquifer with no effective groundwater extraction restrictions only a short distance away from areas where farmers face regulatory limits. This study investigates the effects of policy implementation uncertainty on the extraction of groundwater. An econometric model is estimated for harvested acreage of the three major crops produced in the five representative counties of the Texas High Plains. Corn acreage (an irrigation‐intensive crop) is used as a proxy for groundwater use. After controlling for price and climate effects, it was concluded that there is strong evidence that groundwater use policy uncertainty is likely to increase groundwater extraction in the Texas High Plains region. The social desire to achieve perpetual sustainability of groundwater resources in the study region, or at the very least to prolong the life of the Ogallala Aquifer, has resulted in discussions about alternative groundwater management policies. Producers, in their concern about the implementation of policies to slow down groundwater extraction, increase their use of water in the short‐run in order to maximize profits before groundwater use restriction policies are enforced.